2014
DOI: 10.1007/s11031-014-9414-5
|View full text |Cite
|
Sign up to set email alerts
|

When need for closure leads to positive attitudes towards a negatively stereotyped outgroup

Abstract: The study examined the relationship between epistemic motivation, which is the need for closure (NFC), and positive attitudes towards a negatively stereotyped outgroup (i.e., Gypsies). Although extensive research has revealed that NFC is related to derogatory behavioural tendencies and negative emotions towards stereotyped groups, it is proposed that NFC may also be linked to positive attitudes towards outgroups. It is predicted, however, that this would be true only when NFC is accompanied by a low ability to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 52 publications
2
17
0
4
Order By: Relevance
“…High NFC people are more sensitive to normative pressures (e.g., Fu et al 2007; Jia et al 2014) and might be motivated to not express their stereotypes or prejudices at an explicit level. In fact recently many studies demonstrated the effect of NFC on stereotyping only under certain circumstances (e.g., Kossowska et al 2015; Kossowska and Bar-Tal 2013; Sun et al 2016). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High NFC people are more sensitive to normative pressures (e.g., Fu et al 2007; Jia et al 2014) and might be motivated to not express their stereotypes or prejudices at an explicit level. In fact recently many studies demonstrated the effect of NFC on stereotyping only under certain circumstances (e.g., Kossowska et al 2015; Kossowska and Bar-Tal 2013; Sun et al 2016). …”
Section: Discussionmentioning
confidence: 99%
“…For example, it was shown that high NFC individuals develop stereotypical impressions about the outgroups under self-esteem threat but only when they held explicit prejudiced beliefs towards the outgroup (Kosic et al 2014). However, if high (vs. low) NFC individuals lack a prejudice towards outgroup, their sample new information in their quest for a clear-cut answer, thus may develop less stereotypical evaluations of the outgroups (see also Kossowska et al 2015). …”
Section: Introductionmentioning
confidence: 99%
“…In another set of studies, Kossowska et al (2015) demonstrated that participants with high levels of NFC but low AAC actually exhibited positive attitudes toward a negatively stereotyped out-group (Gypsies). In this study, participants' perception of their AAC was experimentally lowered using a computerized version of a concept formation task, which was originally developed as the Informational Helplessness Training procedure (Sedek & Kofta, 1990).…”
Section: Inability To Achieve Closurementioning
confidence: 99%
“…In particular, manipulations of positive mood or empowerment (Kossowska & Bar-Tal, 2013b;Kossowska, Jaśko, Bar-Tal, & Szastok, 2012, Study 2) increased participants' (perceived) ability to attain closure and, therefore, strengthened the positive association between NFC and heuristic processing. Conversely, manipulations of self-image threat (Kossowska, Bukowski, & Guinote, 2013) or decreased cognitive control (Otten & Bar-Tal, 2002;Kossowska, Dragon, & Bukowski, 2015) lowered participants' ability to attain closure and, therefore, resulted in high NFC being associated with less, rather than more, heuristic processing.…”
Section: Need Versus Ability To Achieve Closurementioning
confidence: 99%
“…However, when the unexpected occurs, or when exposed to unfamiliar contexts such as counter‐stereotypical information, automatic processing becomes insufficient and people rely on it to a lesser extent (e.g., Louis & Sutton, ). In such circumstances, in order to make sense of their new experiences, people may deviate from their default cognitive patterns and begin to notice things they would normally have filtered out (Kossowska, Dragon, & Bukowski, ; Louis & Sutton, ; Tadmor, Hong, Chao, Wiruchnipawan, & Wang, ). In this article, we suggest that expectancy‐inconsistent information provided to participants may lead those high in NFC to deviate from the application of compensatory rules, and that this in turn influences their social perception.…”
Section: Discussionmentioning
confidence: 99%